(3TQM GdJLdjGJs - (3TeS GdOjf CHhWGgQ ESeGYjd Hf ShOcjf Hf YHO Gddg GdfhQjs
(3ChdgG (B:s
(3bGd GdTjN Hf YHOGddg GdfhQj GdMeO ddg GdPj enf Ydi YHGOg GdPjf GUWai HeYQaI eQGJH GdJLdjGJ hLYdge Ydi HUjQI efg aj LejY GdMGdGJ s
(3BNQgG (B:s
(3cja CfJ hcja CfG hef CfJ Odjd GdNGRf eUaj GdbdhH JPcQI GdNhGU hYbjOI Cgd GdENJUGU JeJ s
(3GfXQ GdJLdjGJ GdGdgjg ai cTa GdXfhf L (B1 (3U`(B352s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs